When Does Partisanship Become Excessive?. Issue 3 (3rd July 2018) - Cuddy, Andrew
Abstract : Despite the essential role of political parties, excessive partisanship is often considered detrimental for democracy in general and the functioning of parliament in particular. This article examines the multi-faceted nature of partisanship. First, a number of possible types of excessive partisanship are identified in which a specific aspect or element is taken to a heightened degree. It will be argued that partisanship may become excessive by way of its underlying worldview, electoral ends, uncivil or unethical means, universal scope, or internal culture. Second, this framework allows for a nuanced evaluation of how and why excessive partisanship is problematic for democracy. It will be shown that different hyper-partisan types have varying normative implications.